2010
DOI: 10.1093/cercor/bhq201
|View full text |Cite
|
Sign up to set email alerts
|

Weight Consistency Specifies Regularities of Macaque Cortical Networks

Abstract: To what extent cortical pathways show significant weight differences and whether these differences are consistent across animals (thereby comprising robust connectivity profiles) is an important and unresolved neuroanatomical issue. Here we report a quantitative retrograde tracer analysis in the cynomolgus macaque monkey of the weight consistency of the afferents of cortical areas across brains via calculation of a weight index (fraction of labeled neurons, FLN). Injection in 8 cortical areas (3 occipital plus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

39
480
4

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 353 publications
(533 citation statements)
references
References 109 publications
(187 reference statements)
39
480
4
Order By: Relevance
“…Accordingly, previous studies demonstrated that orthodromic stimulation effects are many times stronger than antidromic effects even between areas with strong direct projections (62,70,71). The direct connectivity between V1 and V4 is relatively sparse (72), and the antidromic contribution to our findings was therefore presumably even smaller than in these previous studies.…”
Section: Discussioncontrasting
confidence: 37%
“…Accordingly, previous studies demonstrated that orthodromic stimulation effects are many times stronger than antidromic effects even between areas with strong direct projections (62,70,71). The direct connectivity between V1 and V4 is relatively sparse (72), and the antidromic contribution to our findings was therefore presumably even smaller than in these previous studies.…”
Section: Discussioncontrasting
confidence: 37%
“…Major progress on this front has come from a recent systematic effort from the laboratory of Henry Kennedy, revealing that connectivity profiles are more highly distributed and that connection strengths span a much wider range than previously realized (Knoblauch et al 2015). Using a 91-area cortical parcellation and retrograde tracers injected into 29 cortical areas, Markov et al (2012) determined that each cortical area receives on average inputs from 55 other areas out of a (minimum) 26 and (maximum) 87; when expressed as the fraction of retrogradely labeled neurons, these pathways vary over five orders of magnitude in connection strength (Markov et al 2011(Markov et al , 2012Knoblauch et al 2015). This translates to 1615 inter-areal pathways out of 2610 possible in a 29 Â 91 connectivity matrix.…”
Section: Distributed Cortical Connectivitymentioning
confidence: 99%
“…Each mm 2 patch of macaque cortex contains~10 5 neurons and may contain~10 9 synapses (but with significant regional variability, as noted above). An estimated 80 % of inputs come from local (intra-areal) circuits, within a radius of several mm of a given patch (Markov et al 2011). The remaining 20 % of long-distance within-hemisphere inputs are distributed across the 10,000-mm 2 surface area of each hemisphere.…”
Section: Distributed Cortical Connectivitymentioning
confidence: 99%
“…An extensive set of studies carried out by Henry Kennedy and colleagues (Markov et al 2011(Markov et al , 2013a(Markov et al , b, 2014 have revealed the connectional anatomy of the macaque cerebral cortex in new detail. Injections of retrograde tracers in 29 cortical areas followed by rigorous quantification of label density across the entire cortex demonstrated a previously unknown degree of connectedness among areas.…”
Section: Macroscalementioning
confidence: 99%
“…Injections of retrograde tracers in 29 cortical areas followed by rigorous quantification of label density across the entire cortex demonstrated a previously unknown degree of connectedness among areas. Numerous new (and mostly relatively weak) projections were uncovered, and the overall connectivity profile for each area was best approximated by a lognormal distribution (Markov et al 2011), with a few strong projections and a large admixture of medium or weak pathways. Graph analysis provided evidence for a relatively high proportion of unidirectional links (Markov et al 2014), a strong contribution of long-distance projections towards areal specificity (Markov et al 2013a), significant distance-dependence of connection densities (Ercsey-Ravasz et al 2013), and hierarchical arrangement of areas into "counter-streams" (Markov et al 2013b).…”
Section: Macroscalementioning
confidence: 99%